2018
DOI: 10.1186/s12943-018-0864-3
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers for predicting efficacy of PD-1/PD-L1 inhibitors

Abstract: Programmed cell death protein 1/programmed cell death ligand 1 (PD-1/PD-L1) is a negative modulatory signaling pathway for activation of T cell. It is acknowledged that PD-1/PD-L1 axis plays a crucial role in the progression of tumor by altering status of immune surveillance. As one of the most promising immune therapy strategies, PD-1/PD-L1 inhibitor is a breakthrough for the therapy of some refractory tumors. However, response rate of PD-1/PD-L1 inhibitors in overall patients is unsatisfactory, which limits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
458
2
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 615 publications
(515 citation statements)
references
References 136 publications
(135 reference statements)
7
458
2
3
Order By: Relevance
“…Additional immune‐oncology markers such as high TMB are under investigation as part of late phase clinical trials . However, it remains to be seen whether immune checkpoint inhibitors will have efficacy for the treatment of EMPD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional immune‐oncology markers such as high TMB are under investigation as part of late phase clinical trials . However, it remains to be seen whether immune checkpoint inhibitors will have efficacy for the treatment of EMPD.…”
Section: Discussionmentioning
confidence: 99%
“…6 Additional immune-oncology markers such as high TMB are under investigation as part of late phase clinical trials. 38,39 However, it remains to be seen whether immune checkpoint inhibitors will have efficacy for the treatment of EMPD. We observed some patients with high TMB and the presence of PD-L1 in IC (TIL) in our study of EMPD, indicating that these F I G U R E 3 The same case provided in Figure 2 with a PD-L1 positivity in the inflammatory (immune cells, IC; upper right image, white arrow); Please note the absence of PD-L1 expression in tumor cells (TC; white arrow); Lower two images show HER2 (left) and TOP2A gene co-amplifications (right image) (Chromogenic in situ hybridization).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that AYA with fusion-positive sarcomas have poorer prognosis compared with younger patients, but to our knowledge there is no comparison with OA in the literature. 11 Extensive genomic characterization has been made of adult STS, 12 but there certainly is a great need for further biological and translocational studies to demonstrate possible differences between AYA and other age groups with the same STS subtype. 5 Factors influencing the possible sensitivity to immunotherapy, such as copy number load, PD-L1 expression, infiltrating T cells, and microsatellite instability, also need to be investigated further.…”
Section: Discussionmentioning
confidence: 99%
“…5 Factors influencing the possible sensitivity to immunotherapy, such as copy number load, PD-L1 expression, infiltrating T cells, and microsatellite instability, also need to be investigated further. 11 Extensive genomic characterization has been made of adult STS, 12 but there certainly is a great need for further biological and translocational studies to demonstrate possible differences between AYA and other age groups with the same STS subtype. Such information could be valuable for interventional studies comparing the efficacy of treatment in AYA compared with OA.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, checkpoint inhibition, and IL-10 treatment together enhances the number and quality of pre-existing TILs. The efficacy of PD-1/PD-L1 inhibitors is highly associated with tumor microenvironment such as TIL density, PD-1/PD-L1 expression; tumor intrinsic feature, such as tumor mutational burden, microsatellite instability; as well as gut microbiota (62). The clinical trials of pegylated recombinant human IL-10 are focused on several solid tumor types.…”
Section: Il-10 Functions As An Immune Activating Cytokine In Cancer Imentioning
confidence: 99%